The physicochemical aspects of DNA sensing using electrochemical methods. - Batchelor-McAuley, C; Wildgoose, G; Compton, R (2009)
As our understanding of the human genome increases there is an ever expanding demand for fast, sensitive and selective methods of DNA analysis. Due to the low associated production costs, and high sensitivity and selectivity of many electrochemical systems, development of these methods holds much promise. Production of a portable low-cost system suitable for DNA analysis has the potential to revolutionise modern health care. Single-nucleotide polymorphisms (SNPs) are a common form of genomic variation. These alterations to the genetic code can cause a change in a given genes' function and as such may increase an individuals susceptibility to a disease. Consequently it is imperative that any system of DNA analysis is able to distinguish between single changes in the base pair sequence. This review aims to build an understanding of DNAs structure and physicochemical properties, focusing on the thermodynamics and kinetics of DNA hybridisation. From this a wide overview of the current methods of electrochemical DNA sensing is provided with the discussion of both labeled and non-labeled methods. Recent work in which DNA sensing has been taken beyond single-analyte detection is also discussed.